New Approaches in Digital Biblical Studies - Beyer, Barbara 198X- (Novum Testamentum, 2026)
Digital approaches to biblical studies have increased in number and significance over the last 20 years. In order to gauge the large spectrum of methodologies, research questions, and research objects, this essay showcases a range of projects that have been included in two volumes of the series Digital Biblical Studies. Using them as a stepping stone, the introductory and concluding remarks seek to map digital biblical studies within the broader field of biblical studies, to reveal common trends, and to offer suggestions for the future interaction of Digital Humanities and biblical studies.